CircPTP4A2-miR-330-5p-PDK2 Signaling Facilitates In Vivo Survival of HuMSCs on SF-SIS Scaffolds and Improves the Repair of Damaged Endometrium. (6th May 2022) - Zheng, Yuanyuan; Li, Linhao; Bi, Xuewei; Xue, Ruyue
Abstract : Background . Human umbilical cord mesenchymal stem cells- (HuMSCs-) based therapy has shown promising results in the treatment of intrauterine adhesions (IUA). In this study, we aimed to construct a HuMSCs-seeded silk fibroin small-intestinal submucosa (SF-SIS) scaffold and evaluate its ability to repair the damaged endometrium in an IUA mouse model. Methods . To identify the functional effect of HuMSCs-SF-SIS scaffolds on the repair of damaged endometrium, a mouse IUA model was established. Uterine morphology and fibrosis were evaluated by hematoxylin-eosin staining and Masson staining. CircRNA sequencing, real-time PCR, and RNA fluorescence in situ hybridization were used to screen and verify the potential circRNAs involved in the repair of damaged endometrium by HuMSCs. Real-time integrated cellular measurement of oxygen consumption rate was performed using the Seahorse XF24 Extracellular Flux Analyzer. The potential downstream miRNAs and proteins of circRNAs were analyzed by dual-luciferase reporter assay and western blot. Results . HuMSCs-SF-SIS not only increased the number of glands but also reduced the ulcer area in the IUA model. circPTP4A2 was elevated in the HuMSCs seeded on the SF-SIS scaffolds and was targeted by miR-330-5p-PDK2. It also stabilized the mitochondrial metabolism of HuMSCs. Moreover, miR-330-5p was found to inhibit PDK2 expression through the 3 ′ UTR target region. A rescue experiment further showed that circPTP4A2-miR-330-5p-PDK2 signaling was critical to HuMSCs-SF-SIS in decreasing the fibrosis area and increasing the number of glands in the IUA model. Conclusion . We demonstrated that circPTP4A2 was elevated in HuMSCs-seeded on SF-SIS scaffolds and stabilized the mitochondrial metabolism through miR-330-5p-PDK2 signaling, which contributes to endometrial repair progression. These findings demonstrate that HuMSCs-seeded SF-SIS scaffolds have potential for the treatment of IUA.